Is initial rhythm in OHCA a predictor of preceding no flow time? Implications for bystander response and ECPR candidacy evaluation. (July 2018) - Tanguay-Rioux, Xavier; Grunau, Brian; Neumar, Robert; Tallon, John; Boone, Robert; Christenson, Jim
Abstract: Objective: Shockable cardiac rhythms are associated with improved outcomes among out-of-hospital cardiac arrests (OHCA). Initial cardiac rhythm may also be predictive of a short preceding no-flow duration. We examined the relationship between no-flow duration and initial cardiac rhythm, which may demonstrate the urgency in rescuer response and assist with candidacy evaluation for extracorporeal-cardiopulmonary resuscitation (ECPR). Methods: We examined consecutive adult OHCA's identified by a prospective registry in British Columbia (2005–2016). We included those with witnessed OHCA but no bystander CPR. The variable of interest was no-flow duration, defined as time from 9-1-1 call to EMS arrival. We fit an adjusted logistic regression model to estimate the association of no-flow duration and initial cardiac rhythm. Among those with shockable initial rhythms, we calculated the cumulative proportion with no-flow durations under incremental time cut-offs. Results: Of 26 621 EMS-treated OHCA's, 2532 were included. Overall survival was 13.8%, and 34% had initial shockable rhythms. The probability of having an initial shockable rhythm decreased with increasing no-flow durations (adjusted OR 0.88 per minute, 95% CI 0.85–0.91). Among those found with initial shockable rhythms, 94% (95% CI 92–96%) had a no-flow time under 10 min. Conclusion: The odds of a shockable initial rhythm declined with each additional minute of no-flow time, highlighting the importance of early access to defibrillation. Among those with initial shockable rhythms, the preceding no-flow duration was highly likely to be under 10 min, which may inform decisions about ECPR candidacy among select patients with unwitnessed arrests.